2010
DOI: 10.1021/jf904335g
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effect of Benifuuki Tea Containing O-Methylated EGCG

Abstract: Benifuuki is a tea cultivar with an antiallergic effect stronger than that of Yabukita tea, the most popular green tea cultivar consumed in Japan. The effective compound is (-)-epigallocatechin-3-O-(3-O-methyl)gallate (EGCG3''Me), an O-methylated derivative of EGCG. This study examined the antihypertensive effects of EGCG3''Me and Benifuuki tea. First, it was determined that EGCG3''Me has a significant inhibitory effect on the activity of angiotensin I-converting enzyme (ACE). Second, clinical trials showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
73
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 18 publications
0
73
0
Order By: Relevance
“…9,10) A clinical trial revealed that Benifuuki tea also had stronger anti-hypertensive effects than those of Yabukita tea. 1) Although EGCG3″Me and the teas containing it have strong bioactivities in vivo, the bioactivities of EGCG3″Me and Benifuuki tea extract in vitro were not stronger than those of EGCG or Yabukita tea extract. 1,10) These findings suggested that the absorption of O-methyl EGCGs and Benifuuki tea extract may be related to their strong bioactivities in vivo.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…9,10) A clinical trial revealed that Benifuuki tea also had stronger anti-hypertensive effects than those of Yabukita tea. 1) Although EGCG3″Me and the teas containing it have strong bioactivities in vivo, the bioactivities of EGCG3″Me and Benifuuki tea extract in vitro were not stronger than those of EGCG or Yabukita tea extract. 1,10) These findings suggested that the absorption of O-methyl EGCGs and Benifuuki tea extract may be related to their strong bioactivities in vivo.…”
mentioning
confidence: 97%
“…1) Although EGCG3″Me and the teas containing it have strong bioactivities in vivo, the bioactivities of EGCG3″Me and Benifuuki tea extract in vitro were not stronger than those of EGCG or Yabukita tea extract. 1,10) These findings suggested that the absorption of O-methyl EGCGs and Benifuuki tea extract may be related to their strong bioactivities in vivo. However, the pharmacokinetics of purified O-methyl EGCGs have not yet been examined.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Beverages: Tea, coffee, and cocoa Green tea, black tea and extracts of active components in both have demonstrated reduction in BP in humans [265][266][267][268][269][270][271] . In a double blind placebo controlled trial of 379 hypertensive subjects given green tea extract 370 mg/d for 3 mo, BP was reduced significantly at 4/4 mmHg with simultaneous decrease in HS CRP, TNF-α, glucose and insulin levels [268] .…”
Section: Sesamementioning
confidence: 99%
“…BF has been reported biomedical activities in human models. 62,111) SR was generated by natural crossbreeding of Nou-6. Compared with Nou-6, this novel cultivar contains high levels of anthocyanins, is high yielding and easy to grow, and shows high resistance to anthracnose and gray blight.…”
Section: Evaluation Of Green Tea Functionality On the Basis Of Imentioning
confidence: 99%